Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja (Studi Kasus Pada Badan Kepegawaian Daerah (BKD) Provinsi Sumatra Barat). - Faisal Arief Budiman; Zefriyenni Zefriyenni; Nila Pratiwi (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Human resources (HR) are very important in an organization, therefore every organization always strives to have quality human resources. Quality human resources in an organization will not work well. Human resources and the organization must have a mutually necessary relationship, the organization needs quality employees and the organization should pay attention to work aspects related to human resources. employee performance at the West Sumatra Province Civil Service Agency (BKD) has not yet reached the target. The research population is all employees. The sampling technique is a saturated sample obtained as many as 72 samples. The analysis tool used is Structural Equation Modeling (SEM). So the results of this study indicate that (1) work motivation has a positive and significant effect (0.162) on job satisfaction at the Regional Civil Service Agency of West Sumatra Province. (2) The work environment has a positive and significant effect (0.000) on job satisfaction at the Regional Civil Service Agency of West Sumatra Province. (3) Work motivation has a positive and significant effect (0.000) on employee performance at the West Sumatra Provincial Civil Service Agency. (4) Work environment has a positive and not significant effect (0.006) on employee performance at the Regional Civil Service Agency of West Sumatra Province. (5) Job satisfaction has a positive and significant effect (0.014) on employee performance at the Regional Civil Service Agency of West Sumatra Province. (6) Work motivation has a positive and significant effect (0.176) on employee performance through job satisfaction at the Regional Civil Service Agency of West Sumatra Province. (7) The work environment has a positive and significant effect (0.018) on employee performance through job satisfaction at the West Sumatra Provincial Civil Service Agency. (8) The contribution of work motivation and work environment variables to job satisfaction is 0.888 or 88.8% and the remaining 11.2% is influenced by other variables not examined in this study at the West Sumatra Provincial Civil Service Agency. (9) The contribution of competency, workload and job satisfaction variables to employee performance is 0.843 or 84.3% and the remaining 15.7% is influenced by other variables not examined by this study at the West Sumatra Provincial Civil Service Agency.